1. Find [f ○ (g ○ h)](2) if f(x) = 2x – 1, g(x) = 4x, and h(x) = x2+ 1.A. 39B. 32C. 47D. 1292. Find f[f(-3)] when f(x) = x2 + 1A. -97B. 83C. 101D. 103. Find [f ○ g](x) if g(x) = x + 1 and f(x) = 2×2 – 5x + 8A. 2×2 – 4x + 9B. 2×2 – x + 5C. 2×2 – 5x + 5D. 2×2 – x + 154. Find [g ○ f](x) if g(x) = x – 4 and f(x) = 3×2. A. 3×2 – 4B. 3×2 - 8x + 16C. 3×2 - 24x + 48D. 3×2 - 485. Find g ○ f if f = {(3, 8), (4, 0), (6, 2), (7, – 1)} and g = {(0,4), (8,6), (3, 6), (-1, 8)}A. {(0,0), (8,2), (3,2)}B. {(0,0), (8,2), (3,2), (-1, 7)}C. {(3, 6), (4, 4), (7, 8)}D. {(3, 6), (4, 4), (6, 3), (6, 8), (7, 8)}6. Find f ○ g if f = {(1,2), (3,4), (5,4)} and g = {(2,5), (4,3)}.A. f ○ g = {(2, 4), (3, 4)}B. f ○ g = {(2, 5), (4, 3)}C. f ○ g = {(2, 5), (4, 3), (5, 2)}D. f ○ g = {(2, 4), (4, 4)}7. A. x3+x2-8x – 12x+2B. x3-4×2-3x + 18x-3C. x2 + 4x + 4D. x2 – 6x + 98. 9. Find (f – g)(x) if f(x) = x2 - x – 6 and g(x) = 2×2 – 3x + 4A. -x2 + 2x – 10B. x2 – 4x – 2C. 3×2 – 4x – 2D. x2 + 2x – 1010. Find (f + g)(x) if f(x) = x2 + 6x + 9 and g(x) = 2x + 6.A. 9×2 + 15B. x2 + 8x + 15 C. 81×2 + 15D. 24x

# 1. Find [f ○ (g ○ h)](2) if f(x) = 2x – 1, g(x) = 4x, an

Tags:Homework Help